2017
DOI: 10.2147/ott.s136549
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the cancer stem cell marker CD117 predicts poor prognosis in epithelial ovarian cancer patients: evidence from meta-analysis

Abstract: 05-3.26). EOC patients with high CD117 expression had significantly worse OS (hazard ratio [HR] =1.39, 95% CI =1.03-1.90) than patients with low CD117 expression. However, no significant correlation was found between CD117 expression and disease-free survival (HR =1.31, 95% CI =0.79-2.17). In subgroup analysis, CD117 was identified as a significant prognostic factor for overall survival in European patients (HR =1.59, 95% CI =1.13-2.23), younger patients (,60 years) (HR =1.59, 95% CI =1.10-2.30), studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The high degree of consistency in MYCN regulation in KD FT and HGSOC organoids from independent donor samples warrants further studies to investigate its potential role as a stemness marker in HGSOC. Also, while we show that surface expression of CD133 correlates with in vitro growth capacity of HGSOC organoids, the exact functional relationship between stemness regulation in the organoid culture and other previously described ovarian cancer stem cell markers CD117, ALDH1 and CD24 (Gao et al, 2010;Kryczek et al, 2012;Yang et al, 2017a) is yet to be tested.…”
Section: Discussionmentioning
confidence: 73%
“…The high degree of consistency in MYCN regulation in KD FT and HGSOC organoids from independent donor samples warrants further studies to investigate its potential role as a stemness marker in HGSOC. Also, while we show that surface expression of CD133 correlates with in vitro growth capacity of HGSOC organoids, the exact functional relationship between stemness regulation in the organoid culture and other previously described ovarian cancer stem cell markers CD117, ALDH1 and CD24 (Gao et al, 2010;Kryczek et al, 2012;Yang et al, 2017a) is yet to be tested.…”
Section: Discussionmentioning
confidence: 73%
“…CD117 + /CD44 + cells isolated from the ascitic fluid of ovarian cancer patients are very sensitive to the anti-cancer stem cell antibiotic salinomycin: this drug added alone induced an inhibition of stemness markers of CD117 + /CD44 + cells, such as SOX2 and OCT 3-4 and added together with paclitaxel induced apoptosis of these cells [ 244 ]. About 25% of HGS-OvCa patients display overexpression of CD117; a meta-analysis on more than 1200 patients reported in literature clearly showed that CD117 overexpression was associated with reduced overall survival [ 245 ].…”
Section: Ovarian Cancer Stem Cellsmentioning
confidence: 99%
“…A meta-analysis of selected CD117 studies showed the relation between CD117 status and several clinical parameters including: age, FIGO stage, tumor grade, histological type. High CD117 expression meant worse OS but no correlation with DFS was found [ 66 ].…”
Section: Clinical and Prognostic Relevance Of Surface Markersmentioning
confidence: 99%